A Study of Relationship between Culture, Gender and Sustainable Tourism: A Study of Bhutan - Sharma, Swati (Journal of Environmental Accounting and Management, 2026)
The effect of tourism on environment is a subject of growing concern. Increasing environmental consciousness has made sustainable tourism management a current issue. This paper aims at exploring the relationship between culture (i.e. long term orientation and indulgence vs. restraint), gender and the attitude towards sustainable tourism. This study follows a descriptive co-relational design. The data was collected from the indigenous residents of Bhutan. Out of 500 responses received 249 were found complete and usable. The findings of the study reveal significant relationships between the dimensions of sustainable tourism, gender and culture viz., long term orientation, and indulgence v/s restraint. This study contributes to the knowledge base of sustainable tourism with respect to restricted tourism policy of the Kingdom of Bhutan. The results indicate a strong positive relationship between cultural values and sustainable tourism. The findings will enable government and policy makers to determine the public reaction toward tourism development, proposed governments policies and legislations on sustainable tourism development.